2019
DOI: 10.7150/jca.30074
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67/MKI67 as a Predictive Biomarker for Clinical Outcome in Gastric Cancer Patients: an Updated Meta-analysis and Systematic Review involving 53 Studies and 7078 Patients

Abstract: Gastric cancer (GC) threatens human health worldwide and we performed this meta-analysis to evaluate the clinical value of Ki-67/MKI67 in patients with GC. The combined hazard ratio (HR), odds ratio (OR) and 95% confidence interval (95% CI) were calculated to assess the relationships of Ki-67/MKI67 expression with prognoses and clinicopathological characteristics. Genes co-expressed with MKI67 were collected for Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and protein-protein inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 63 publications
2
31
2
1
Order By: Relevance
“…Marker of proliferation Ki-67 (MKI67) is a proliferation-related nucleus protein gene that is widely expressed in proliferating cells [52]. Previous studies have reported the abnormally high expression of MKI67 in multiple types of cancer, including CRC, and found that MKI67 could be an independent prognostic biomarker in these types of cancer [53]. However, these genes above in our study were not significantly associated with the prognosis in CRC patients.…”
Section: Mki67contrasting
confidence: 77%
“…Marker of proliferation Ki-67 (MKI67) is a proliferation-related nucleus protein gene that is widely expressed in proliferating cells [52]. Previous studies have reported the abnormally high expression of MKI67 in multiple types of cancer, including CRC, and found that MKI67 could be an independent prognostic biomarker in these types of cancer [53]. However, these genes above in our study were not significantly associated with the prognosis in CRC patients.…”
Section: Mki67contrasting
confidence: 77%
“…Xiong retrospectively analyzed multiple studies of 7,078 patients and found that high expression of MKI67 reduced the overall survival rate and tumor‐free survival rate. Further functional analysis revealed that MKI67 might take part in the occurrence of apoptosis by regulating the p53 signaling pathway (Xiong, Zeng, Jiang, Luo, & Chen, 2019). Furthermore, Zeng demonstrated that SNRPA1 (OMIM: 603521) can regulate PIK3R1 (OMIM:171833) , VEGFC (OMIM:601528) , and MKI67 molecules in colorectal cancer through gene overexpression and gene knockout experiments, and then be involved in tumorigenesis and development, suggesting that MKI67 may serve as a molecular target for cell cycle and apoptosis (Zeng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“… 10 Moreover, it is a predictive biomarker involved in breast cancer diagnosis. 11 Different studies have reported the clinical and prognostic roles of Ki-67 in different types of cancers such as gastric cancer 12 and breast cancer. 13 Besides, Ki-67 expression can be mediated by specific miRNA–mRNA interactions.…”
Section: Introductionmentioning
confidence: 99%